Wang Yao Zang xue wen ji Tubo jian du zong lu, Zang yu wen yan jiu = Tubo jian du zong lu, Zang yu wen yan jiu = Zang yu wen yan jiu - Wang, Yao (Zhongguo Zang xue chu ban she, 2012)
Summary in vernacular field only
Keywords: Inscriptions, Tibetan / History and criticism; Tibetan language; Inscriptions, Tibetan; Geschichte; Tibet Autonomous Region (China) / History; China / Tibet Autonomous Region